Oxidative stress, DNA damage, inflammation and gene expression in occupationally exposed university hospital anesthesia providers - Souza, Kátina Meneghetti [UNESP] (2021)
Considering the importance and lack of data of toxicogenomic approaches on occupational exposure to anesthetics, we evaluated possible associations between waste anesthetic gases (WAGs) exposure and biological effects including oxidative stress, DNA damage, inflammation, and transcriptional modulation. The exposed group was constituted by anesthesia providers who were mainly exposed to the anesthetics sevoflurane and isoflurane (10 ppm) and to a lesser degree to nitrous oxide (150 ppm), and the control group was constituted by physicians who had no exposure to WAGs. The oxidative stress markers included oxidized DNA bases (comet assay), malondialdehyde (high-performance liquid chromatography [HPLC]), nitric oxide metabolites (ozone-chemiluminescence), and antioxidative markers, including individual antioxidants (HPLC) and antioxidant defense marker (ferric reducing antioxidant power by spectrophotometry). The inflammatory markers included high-sensitivity C-reactive protein (chemiluminescent immunoassay) and the proinflammatory interleukins IL-6, IL-8 and IL-17A (flow cytometry). Telomere length and gene expression related to DNA repair (hOGG1 and XRCC1), antioxidant defense (NRF2) and inflammation (IL6, IL8 and IL17A) were evaluated by real-time quantitative polymerase chain reaction. No significant differences (p >.0025) between the groups were observed for any parameter evaluated. Thus, under the conditions of the study, the findings suggest that occupational exposure to WAGs is not associated with oxidative stress or inflammation when evaluated in serum/plasma, with DNA damage evaluated in lymphocytes and leucocytes or with molecular modulation assessed in peripheral blood cells in university anesthesia providers. However, it is prudent to reduce WAGs exposure and to increase biomonitoring of all occupationally exposed professionals.